Unsaturated aliphatic ester polylactic acid graft copolymer as well as preparation method and application thereof
By using a method for preparing polylactic acid copolymers grafted with unsaturated aliphatic esters, the problems of insufficient toughness and heat resistance of polylactic acid materials have been solved, resulting in high molecular weight polylactic acid materials with significant modification effects, suitable for agricultural mulch films, food packaging, and medical and hygiene products.
Patent Information
- Application Number
- CN202310813464.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-07-05
AI Technical Summary
In existing polylactic acid (PLA) preparation and modification processes, the quality requirements of lactide monomer raw materials are high, the content of free hydroxyl groups affects the degree of polymerization, PLA products have poor heat resistance and low toughness, simple modification methods have no significant improvement effect, and the modification reactivity of macromolecular chains is low.
A method for preparing unsaturated aliphatic ester-grafted polylactic acid copolymers was adopted. The unsaturated aliphatic ester was grafted with L-lactide, and the mixture was prepolymerized at low temperature and then polymerized at high temperature to prepare high molecular weight unsaturated aliphatic ester-grafted polylactic acid materials. The introduction of polar groups of unsaturated aliphatic esters improved the toughness and heat resistance.
It improves the toughness and elongation at break of polylactic acid materials, enhances the glass transition temperature, makes the material green and biodegradable, easy to industrialize, and retains the terminal hydroxyl groups for further modification.
Smart Images

Figure CN119264390A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a technology for synthesizing polylactic acid through ring-opening polymerization of lactide, in particular to a method for preparing unsaturated aliphatic ester grafted polylactic acid, and belongs to the field of polymer material synthesis. Background Art
[0002] With the continuous development of the economy and society, people's production and daily lives are becoming increasingly dependent on fossil energy. However, non-renewable energy sources such as oil and coal are currently in short supply, and their consumption causes severe environmental pollution. Petroleum-based materials are non-degradable, necessitating the search for green alternatives to petroleum to alleviate the pressure of resource shortages. Consequently, research on bio-based composites has become a hot topic in academia and industry in recent years, aiming to reduce the environmental impact of fossil energy consumption. Compared to polyolefins and polyethylene terephthalate (PET), which are commonly used in industrialized products, polylactic acid (PLA) offers superior strength and processing properties. It is a thermoplastic resin produced by polymerizing lactic acid monomers, which can be fermented from plants such as corn, potatoes, cotton, and hemp. Lactic acid is a renewable raw material and offers advantages such as high strength, good processability, and excellent mechanical properties. However, PLA also has some drawbacks, such as brittleness, strong hydrophobicity, low impact strength, and high price. Furthermore, PLA suffers from poor stability at high temperatures and certain humidity levels, which limits its application.
[0003] Currently, there are two main technologies for producing polylactic acid (PLA) both domestically and internationally (a one-step method and a two-step method). The one-step method uses a protonic acid or metal oxide catalyst to directly polymerize lactic acid under vacuum and heating conditions to produce PLA. However, this method produces a low molecular weight PLA, making it unsuitable for industrial application. Industrial production of PLA often uses a two-step method: in the first step, lactic acid is reacted with a catalyst to produce lactide. In the second step, ring-opening polymerization is performed under reduced pressure and a catalyst to produce PLA. Purification technology is then used to obtain a high-optical-purity PLA material. There are many key factors that affect the preparation of polylactic acid. First, the optical purity of the lactide raw material for synthesizing polylactic acid must be no less than 99%. In addition, the free acid and water molecules remaining in the lactide preparation process will also affect the polymerization of polylactic acid; secondly, the polymerization mechanism of polylactic acid synthesized from lactide can be divided into cationic ring-opening polymerization, anionic ring-opening polymerization and coordination polymerization, and the polymerization mode will also be different when different catalysts are used. The ring-opening polymerization of lactide to synthesize polylactic acid is prone to racemization and oxidation reactions under high temperature reaction conditions, which has a certain impact on the purity of the product; finally, the residual lactide monomer in the polylactic acid product that has not participated in the ring-opening polymerization needs to be removed in a timely manner, otherwise it will affect the purity and molecular weight of the polylactic acid product.
[0004] Polylactic acid has the disadvantages of being brittle, highly hydrophobic, and having low toughness. Therefore, it is difficult to directly prepare industrial products from polylactic acid materials like general-purpose plastics such as polyethylene and polypropylene, and it must be modified and processed. Currently, the most commonly used method is to optimize its performance by blending polylactic acid with other plastics. Although this method is simple, it does not fundamentally change the properties of polylactic acid materials. In addition, some studies have plasticized and toughened polylactic acid materials, adding toughening agents, plasticizers, or cross-linking agents to polylactic acid materials or materials blended with other resins to improve the shortcomings of polylactic acid's high brittleness and low toughness. Although this has improved the thermodynamic properties of polylactic acid materials to a certain extent, the modification effect is not significant.
[0005] Chinese patent CN105504729A mixes glycidyl methacrylate, methyl (meth)acrylate, butyl (meth)acrylate, γ-methacryloxypropyltrimethoxysilane, and initiator dicumyl peroxide in a mass ratio of 15:20:50:15:0.5 to form a mixed solution, and then mixes the mixed solution with poly (L-lactic acid) (molecular weight 5×10 4) are added into a blender in a mass ratio of 1:1 and mixed evenly, and then put into a twin-screw extruder for melt extrusion and granulation at a temperature of 190°C. The screw speed is adjusted so that the material residence time is 8 minutes, and the product modified polylactic acid material is obtained by granulation; although the matrix polylactic acid and the filler are chemically bonded by a modified coupling agent, thereby forming an elastomer with a certain thickness between the two, thereby achieving the effect of improving toughness and adhesion, the simple linking method between the macromolecular chains has limited modification effect on the polylactic acid. Chinese Patent No. 106519195A reacts methyl methacrylate with hydroxyethyl methacrylate monomers to obtain a macromolecular initiator containing terminal hydroxyl groups in the side chain, which then initiates the ring-opening polymerization of cyclic ester monomers (such as glycolide, lactide or caprolactone) to obtain a comb-like polyester; the comb-like polyester is then blended with polylactic acid and electrospun to obtain modified polylactic acid fibers. The comb-like polyester main chain is a methyl methacrylate-hydroxyethyl methacrylate copolymer structure, which is flexible and elastic, and has a toughening and strengthening effect on the polylactic acid matrix. By adjusting the ratio of polymethyl methacrylate and polyhydroxyethyl methacrylate chain segments in the copolymer structure, polylactic acid fibers with different modification effects can be obtained. Although the polyester carrying polyester side chains solves the problem of poor compatibility between the main chain and polylactic acid, the toughness modification effect of the polylactic acid is not significant because only the polylactic acid end groups carry polyester side chains. Chinese Patent No. 108129813A provides a polylactic acid resin composition for injection molding materials, which includes 70% to 95% polylactic acid resin and 5.0% to 30% modified masterbatch. The modified masterbatch contains a double-crosslinked copolymer A and a copolymer B having a core-shell structure, wherein the shell layer of copolymer A is poly (D-lactic acid) and the core layer is a cross-linked acrylate-glycidyl methacrylate copolymer, and the two form a secondary crosslink; the shell layer of copolymer B is poly (L-lactic acid) and the core layer is a cross-linked acrylate-glycidyl methacrylate copolymer, and the two form a secondary crosslink; the weight ratio of copolymer A to copolymer B is 2:3 to 3:2. This technology can achieve better toughening and heat resistance for polylactic acid, but does not fundamentally change the thermodynamic properties of polylactic acid.
[0006] In summary, the current processes for the preparation and modification of polylactic acid have the following major problems: (1) High quality requirements for the lactide monomer raw material. The free hydroxyl content (free acid and water) in the lactide monomer seriously affects the degree of polylactic acid polymerization. (2) Pure polylactic acid products have poor heat resistance and low toughness, and require modification processing for industrial application. (3) Simply adding plasticizers and toughening agents to polylactic acid materials cannot fundamentally improve the thermodynamic properties of polylactic acid. (4) Grafting or esterification reactions on the side chains or end groups of the polylactic acid macromolecular chain have low reactivity and poor modification effects. Summary of the Invention
[0007] In response to the above shortcomings, the present invention provides an unsaturated aliphatic ester grafted polylactic acid copolymer and a preparation method thereof. A reaction route different from the prior art is adopted to prepare an unsaturated aliphatic ester grafted polylactic acid material with a higher molecular weight. The grafting rate of the unsaturated aliphatic ester is high. The unsaturated aliphatic ester grafted polylactic acid copolymer has good toughness and heat resistance, is green and degradable, and is easy to industrialize.
[0008] In order to achieve the above technical objectives, the technical solutions adopted by the present invention are as follows:
[0009] The technical purpose of the first aspect of the present invention is to provide an unsaturated fatty ester grafted polylactic acid copolymer, which is a compound having the general formula I structure:
[0010]
[0011] Where R1, R2, ... and R n are independently selected from H or wherein R is a C1-C6 substituted or unsubstituted alkyl group, preferably a C1-C4 substituted or unsubstituted alkyl group, and R1, R2, ... and R n for The number of groups accounts for R1, R2, ... and R n The molar percentage of the total amount is not less than 25%, preferably not less than 30%, more preferably not less than 35%, and most preferably not less than 40%.
[0012] Furthermore, the weight average molecular weight of the copolymer is 1.5×10 5 -4.5×10 5 , preferably 2.5×10 5 -4.0×10 5 .
[0013] Furthermore, the copolymer has a right-angle tear strength of not less than 130 kN / m, preferably 135-155 kN / m; an elongation at break of not less than 35%, preferably 40-55%, and a glass transition temperature of 85-100°C.
[0014] In the present invention, the right-angle tear strength and elongation at break are measured by a universal mechanical testing machine; the weight-average molecular weight is measured by gel permeation chromatography; and the glass transition temperature is measured by a differential scanning calorimeter. Details are described below.
[0015] The technical purpose of the second aspect of the present invention is to provide a method for preparing an unsaturated aliphatic ester grafted polylactic acid copolymer, comprising the following contents:
[0016] (1) L-lactide, and an initiator to react with each other to obtain an unsaturated fatty ester grafted L-lactide product (HEM-LLA), which is then purified; wherein, Wherein R is a C1-C6 substituted or unsubstituted alkyl group;
[0017] (2) mixing the HEM-LLA obtained in (1) with a catalyst and an initiator, and prepolymerizing at low temperature to obtain a HEM-LLA oligomer;
[0018] (3) The HEM-LLA oligomer obtained in (2) is mixed with an antioxidant and polymerized at high temperature to obtain an unsaturated aliphatic ester grafted polylactic acid copolymer (HEM-PLLA).
[0019] Furthermore, the initiator in step (1) is dicumyl peroxide or 2,5-dimethyl-2,5-bis-(tert-butylperoxy)hexane, preferably dicumyl peroxide; and the amount of the initiator added is 1-10% by weight, preferably 1-5% by weight, of the L-lactide.
[0020] Furthermore, step (1) is carried out under a constant temperature reaction in an inert gas flow, preferably a nitrogen flow, and vacuum conditions, the reaction temperature is 50-150°C, preferably 80-120°C, the reaction pressure is 2-100kPa, preferably 20-60kPa; the reaction time is 1-20h, preferably 2-10h; the gas flow rate of the nitrogen flow protection is 0.5-6m / s, preferably 2-4m / s; the is one or more of methyl methacrylate, ethyl methacrylate and butyl methacrylate, preferably ethyl methacrylate, based on the weight of L-lactide, The addition amount is 150-350% of L-lactide, preferably 200-300%.
[0021] Furthermore, the optical purity of the L-lactide in step (1) is 99.0-99.6%, preferably 99.4-99.6%, and the L-lactide is homemade or purchased.
[0022] Furthermore, the purification in step (1) is performed by vacuum distillation to remove L-lactide that does not participate in the grafting reaction, thereby obtaining purified unsaturated fatty ester-grafted L-lactide (HEM-LLA). Specifically, the vacuum distillation temperature is 100-200°C, preferably 120-150°C; the pressure is 0-100 kPa, preferably 10-50 kPa; and the time is 1-10 hours, preferably 2-6 hours.
[0023] The main reaction in step (1) is shown below:
[0024]
[0025] Furthermore, the catalyst in step (2) is selected from one or more of stannous octoate, zinc lactate, trialkylaluminum, triisobutylaluminum and stannous chloride, preferably stannous octoate; and the initiator is selected from at least one of glycerol, xylitol, ethylene glycol and triphenylphosphine, preferably triphenylphosphine.
[0026] Furthermore, in step (2), the amount of the catalyst added is 0.1-5% by weight of the HEM-LLA, preferably 0.5-3% by weight; the amount of the initiator added is 0.05-5.0% by weight of the HEM-LLA, preferably 0.5-2%.
[0027] Furthermore, step (2) is a low-temperature polymerization under an inert gas flow, preferably a nitrogen flow, and negative pressure conditions, the polymerization reaction temperature is 100-150°C, preferably 120-140°C; the reaction time is 2-15h, preferably 3-8h; the reaction pressure is 100-1000kPa, preferably 200-500kPa; the gas flow rate of the nitrogen flow is 0.5-6m / s, preferably 2-4m / s.
[0028] Furthermore, the antioxidant in step (3) is one of phosphites, alkyl polyphenols and thiobisphenols, preferably triphenyl phosphite, and the amount of the antioxidant added is 0.1%-5% by weight of the HEM-LLA oligomer, preferably 1-3%.
[0029] Furthermore, the polymerization reaction temperature in step (3) is 150-250°C, preferably 160-200°C.
[0030] Furthermore, step (3) uses a twin-screw extruder to realize the reaction process, adds HEM-LLA oligomer and antioxidant to the twin-screw extruder for polymerization reaction, and performs high-temperature reactive mixing and extrusion granulation to finally obtain an unsaturated fatty ester grafted polylactic acid copolymer material (HEM-PLLA).
[0031] The main reaction process of steps (2) and (3) is shown below:
[0032]
[0033] The technical purpose of the third aspect of the present invention is to provide applications of the above-mentioned polylactic acid graft copolymer, which is used in the fields of agricultural mulch films, food packaging, and medical hygiene products.
[0034] Compared with the existing technology, the present invention has the following advantages:
[0035] (1) Compared with the prior art, the present invention provides a new route for synthesizing polylactic acid graft copolymers. First, unsaturated fatty ester (HEM) is grafted onto L-lactide (LLA) to obtain unsaturated fatty ester grafted L-lactide (HEM-LLA). Then, HEM-LLA is prepolymerized at low temperature to obtain HEM-LLA oligomers. Finally, the HEM-LLA oligomers are polymerized at high temperature to obtain high molecular weight unsaturated fatty ester grafted polylactic acid copolymers.
[0036] (2) The method of the present invention carries out a grafting reaction of unsaturated fatty esters before the polymerization of lactide, which greatly improves the grafting efficiency and increases the molecular weight of the polymer. More unsaturated fatty ester polar groups are successfully introduced into the side chains of polylactic acid through the grafting reaction, thereby improving the toughness and elongation at break of the polylactic acid material. In addition, by adopting the preparation method provided by the present invention, a polylactic acid graft copolymer with a grafting rate of 50% or even 100% can be obtained in theory. By adjusting the raw material ratio, the content of the grafted group in the polylactic acid graft copolymer can be effectively controlled, thereby adjusting the performance of the polylactic acid graft copolymer.
[0037] (3) Due to the introduction of a large number of unsaturated fatty ester structures on the side chains of polylactic acid, the glass transition temperature of the polylactic acid material is increased, and the prepared grafted modified polylactic acid copolymer material is green and fully biodegradable.
[0038] (4) Since the product of the present invention retains the terminal hydroxyl groups of the polylactic acid graft copolymer, the polylactic acid graft copolymer can be further modified through the functional groups to further regulate the properties of the polylactic acid graft copolymer.
[0039] (5) The bulk prepolymerization of L-lactide is carried out in a reactor and then coupled with a twin-screw extruder for copolymerization. The reaction operation is simple and easy to industrialize.
[0040] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The infrared absorption spectra of HEM-LLA and PLLA (polylactic acid), the products of Example 1. DETAILED DESCRIPTION
[0042] The following non-limiting examples can enable those of ordinary skill in the art to more fully understand the present invention, but do not limit the present invention in any way. The reagents, materials, and instruments involved in the following examples, unless otherwise specified, can all be obtained through regular commercial channels. The tests and inspection methods involved in the following examples, unless otherwise specified, are all existing tests and inspection methods in the prior art. The following examples clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Any obvious changes or modifications drawn by the present invention still fall within the scope of protection of the present invention.
[0043] The following are the test methods for the performance parameters involved in the examples:
[0044] (1) Grafting rate of grafted groups:
[0045] The grafting rate of the grafted groups in the polylactic acid graft copolymer was determined by a chemical titration method. Specifically, a certain mass of the polylactic acid graft copolymer was weighed and placed in a conical flask. A certain amount of tetrahydrofuran was added to dissolve it, and a small amount of thymol blue / DMF indicator was added dropwise. The mixture was titrated with an excess of 0.05 mol / L potassium hydroxide in ethanol and back-titrated with 0.01 mol / L HCl-isopropanol solution.
[0046] Grafting rate = n2 / n1×100%, n1 = (m0-m2) / M1, n2 = m2 / M2, that is, grafting rate = [(0.05V KOH -0.01V HCl )×2×M1] / [m0-(0.05V KOH -0.01V HCl )×2×M2]; where m0 is the mass of the weighed polylactic acid graft copolymer, in g; m2 is the total mass of the grafted groups on the polylactic acid molecular chain, calculated based on the consumed KOH; n1 is the degree of polymerization of polylactic acid, i.e., the amount of substance of the lactic acid unit, n2 is the amount of substance of the grafted groups on the polylactic acid molecular chain, M1 is the molar mass of lactic acid, M2 is the molar mass of the grafted groups, V KOH V is the volume of potassium hydroxide ethanol solution added, in mL; HCl The volume of HCl-isopropanol solution consumed in the titration, in mL.
[0047] (2) Right-angle tear strength and elongation at break: measured using a universal mechanical testing machine in accordance with GB / T1039-1992.
[0048] (3) Glass transition temperature: measured using a differential scanning calorimeter (DSC) (DSC 204, NETZSCH, Germany). The test conditions are as follows: sample weight 5-10 mg, first heating the sample from room temperature to 200°C at a heating rate of 10°C / min, and isothermally maintaining the sample for 5 min to eliminate the thermal history; then rapidly cooling the sample to -20°C, and then heating it from -20°C to 200°C at a heating rate of 10°C / min; nitrogen was introduced as a protective gas throughout the test, and the nitrogen flow rate was set at 50 mL / min.
[0049] (4) Polymer weight-average molecular weight: The molecular weight of the polylactic acid graft copolymer samples was characterized by gel permeation chromatography (GPC) using a Waters 1515 system. Chromatographically pure THF was used as the mobile phase at a flow rate of 1.0 ml / min and a column temperature of 35°C. Prior to testing, the sample was dissolved in THF at a concentration of 5 mg / mL and filtered through a polytetrafluoroethylene (PTFE) membrane with a pore size of 0.22 μm before injection. Calibration was performed using a narrow distribution polystyrene (PS) standard.
[0050] (5) Detection of terminal hydroxyl groups: Detected by phthalic anhydride method in accordance with GB / T 12008.3-2009 standard.
[0051] Example 1
[0052] (1) L-lactide and ethyl methacrylate are added to a reactor, and dicumyl peroxide is added as an initiator. The reaction is carried out at a constant temperature under a nitrogen flow and vacuum conditions to obtain ethyl methacrylate-branched L-lactide. The reaction temperature for the graft modification is 95°C, the reaction pressure is 35 kPa, the reaction time is 2 hours, and the nitrogen flow rate is 2 m / s. Based on the weight of the L-lactide, the ethyl methacrylate content is 200% of the L-lactide, and the dicumyl peroxide content is 1% of the L-lactide.
[0053] (2) The L-lactide that did not participate in the grafting reaction in step (1) was removed by vacuum distillation to obtain purified ethyl methacrylate grafted L-lactide (HEM-LLA); the vacuum distillation temperature was 125° C., the pressure was 15 kPa, and the time was 2 h.
[0054] (3) Prepolymerizing the ethyl methacrylate grafted L-lactide (HEM-LLA) obtained in step (2) at low temperature under the action of a catalyst and an initiator, while adding a nitrogen flow and negative pressure to obtain a HEM-LLA oligomer; the reaction temperature of the low temperature prepolymerization is 130° C., the reaction time is 3 h, the reaction pressure is 300 kPa, the gas flow rate of the nitrogen flow protection is 3 m / s, and based on the weight of the ethyl methacrylate grafted L-lactide (HEM-LLA), the catalyst stannous octoate is 0.5% of the HEM-LLA; the initiator triphenylphosphine is 0.2% of the HEM-LLA.
[0055] (4) The HEM-LLA oligomer of step (3) is added to a twin-screw extruder for polymerization reaction, and an antioxidant is added at the same time, and reactive mixing and extrusion granulation are performed at high temperature to finally obtain an ethyl methacrylate grafted polylactic acid copolymer material (HEM-PLLA); based on the weight of the HEM-LLA oligomer, the antioxidant triphenyl phosphite is 0.5% of the HEM-LLA oligomer, and the reactive extrusion temperature of the twin-screw extruder for reactive mixing and extrusion granulation is 180°C.
[0056] Performance characterization: The right-angle tear strength of the ethyl methacrylate grafted polylactic acid copolymer material was measured to be 140 kN / m, the elongation at break was 40%, the glass transition temperature was 85 °C, and the molecular weight of the polymer was 2.1×10 5 The ethyl acrylate grafting rate of the polymer was determined to be 36.2% by chemical titration. The presence of terminal hydroxyl groups was determined by chemical titration.
[0057] Figure 1 The infrared absorption spectra of the products HEM-LLA and PLLA (polylactic acid) of Example 1 are shown in FIG. Figure 1 It can be seen that both are at 2998cm -1 There is an asymmetric stretching vibration peak of CH at 1750cm -1 There is a characteristic absorption peak of C=O group at 1190cm -1 and 1100cm -1 The stretching vibration peak of COC in PLLA is shown in Figure 2. -1 The characteristic absorption peak of -CH2- appears at , indicating that ethyl methacrylate is successfully grafted onto the macromolecular chain of PLLA in the form of free radicals under the action of the initiator.
[0058] Example 2
[0059] (1) L-lactide and ethyl methacrylate were added to a reactor, and dicumyl peroxide (DIPO) was added as an initiator. The reaction was carried out at a constant temperature under a nitrogen flow and vacuum conditions to obtain ethyl methacrylate grafted onto L-lactide. The grafting modification reaction temperature was 100°C, the reaction pressure was 35 kPa, the reaction time was 3 hours, and the nitrogen flow rate was 2.5 m / s. Based on the weight of L-lactide, the ethyl methacrylate content was 220% of the L-lactide, and the dicumyl peroxide content was 2% of the L-lactide.
[0060] (2) The L-lactide that did not participate in the grafting reaction in step (1) was removed by vacuum distillation to obtain purified ethyl methacrylate grafted L-lactide (HEM-LLA); the vacuum distillation temperature was 130° C.; the pressure was 15 kPa, and the time was 2.5 h.
[0061] (3) Prepolymerizing the ethyl methacrylate grafted L-lactide (HEM-LLA) obtained in step (2) at low temperature under the action of a catalyst and an initiator, while adding a nitrogen flow and negative pressure to obtain a HEM-LLA oligomer; the reaction temperature of the low temperature prepolymerization is 135° C., the reaction time is 4 hours, the reaction pressure is 350 kPa, the gas flow rate of the nitrogen flow protection is 3 m / s, and based on the weight of the ethyl methacrylate grafted L-lactide (HEM-LLA), the catalyst stannous octoate is 0.6% of the HEM-LLA; the initiator triphenylphosphine is 0.25% of the HEM-LLA.
[0062] (4) The HEM-LLA oligomer of step (3) is added to a twin-screw extruder for polymerization reaction, and an antioxidant is added at the same time, and reactive mixing and extrusion granulation are performed at high temperature to finally obtain an ethyl methacrylate grafted polylactic acid copolymer material (HEM-PLLA); based on the weight of the HEM-LLA oligomer, the antioxidant triphenyl phosphite is 0.6% of the HEM-LLA oligomer, and the reaction extrusion temperature of the twin-screw extruder for reactive mixing and extrusion granulation is 180°C.
[0063] Performance characterization: The right-angle tear strength of the ethyl methacrylate grafted polylactic acid copolymer material was measured to be 144 kN / m, the elongation at break was 43%, the glass transition temperature was 87 °C, and the molecular weight of the polymer was 2.3 × 10 5 The ethyl methacrylate grafting rate of the polymer was determined to be 38.1% by chemical titration. The presence of terminal hydroxyl groups was determined by chemical titration.
[0064] Example 3
[0065] (1) L-lactide and ethyl methacrylate are added to a reactor, and dicumyl peroxide (DIPO) is added as an initiator. The reaction is carried out at a constant temperature under a nitrogen flow and vacuum conditions to obtain ethyl methacrylate grafted onto L-lactide. The grafting modification reaction temperature is 100°C, the reaction pressure is 40 kPa, the reaction time is 3 hours, and the nitrogen flow rate is 3 m / s. Based on the weight of L-lactide, the ethyl methacrylate content is 240% of the L-lactide, and the dicumyl peroxide content is 3% of the L-lactide.
[0066] (2) The L-lactide that did not participate in the grafting reaction in step (1) was removed by vacuum distillation to obtain purified ethyl methacrylate grafted L-lactide (HEM-LLA); the vacuum distillation temperature was 130° C., the pressure was 20 kPa, and the time was 3 h.
[0067] (3) The ethyl methacrylate grafted L-lactide (HEM-LLA) obtained in step (2) is subjected to low-temperature prepolymerization under the action of a catalyst and an initiator, while adding a nitrogen flow and negative pressure to obtain a HEM-LLA oligomer; the reaction temperature of the low-temperature prepolymerization is 135° C., the reaction time is 4.5 h, the reaction pressure is 350 kPa, the gas flow rate of the nitrogen flow protection is 3.5 m / s, and based on the weight of the ethyl methacrylate grafted L-lactide (HEM-LLA), the catalyst stannous octoate is 0.65% of the HEM-LLA; the initiator triphenylphosphine is 0.3% of the HEM-LLA.
[0068] (4) The HEM-LLA oligomer of step (3) is added to a twin-screw extruder for polymerization reaction, and an antioxidant is added at the same time, and reactive mixing and extrusion granulation are performed at high temperature to finally obtain an ethyl methacrylate grafted polylactic acid copolymer material (HEM-PLLA); based on the weight of the HEM-LLA oligomer, the antioxidant triphenyl phosphite is 0.6% of the HEM-LLA oligomer, and the reactive extrusion temperature of the twin-screw extruder for reactive mixing and extrusion granulation is 185°C.
[0069] Performance characterization: The right-angle tear strength of the ethyl methacrylate grafted polylactic acid copolymer material was measured to be 150 kN / m, the elongation at break was 48%, the glass transition temperature was 90 °C, and the molecular weight of the polymer was 2.46 × 10 5 The ethyl methacrylate grafting rate of the polymer was determined to be 39.5% by chemical titration. The presence of terminal hydroxyl groups was determined by chemical titration.
[0070] Example 4
[0071] (1) L-lactide and ethyl methacrylate were added to a reactor, and dicumyl peroxide (DIPO) was added as an initiator. The reaction was carried out at a constant temperature under a nitrogen flow and vacuum conditions to obtain ethyl methacrylate grafted onto L-lactide. The grafting modification reaction temperature was 105°C, the reaction pressure was 45 kPa, the reaction time was 3.5 hours, and the nitrogen flow rate was 3 m / s. Based on the weight of L-lactide, the ethyl methacrylate content was 260% of the L-lactide, and the dicumyl peroxide content was 4% of the L-lactide.
[0072] (2) The L-lactide that did not participate in the grafting reaction in step (1) was removed by vacuum distillation to obtain purified ethyl methacrylate grafted L-lactide (HEM-LLA); the vacuum distillation temperature was 130° C., the pressure was 25 kPa, and the time was 3.5 h.
[0073] (3) Prepolymerizing the ethyl methacrylate grafted L-lactide (HEM-LLA) obtained in step (2) at low temperature under the action of a catalyst and an initiator, while adding a nitrogen flow and negative pressure to obtain a HEM-LLA oligomer; the reaction temperature of the low temperature prepolymerization is 140° C., the reaction time is 4.5 h, the reaction pressure is 350 kPa, the gas flow rate of the nitrogen flow protection is 3.5 m / s, and based on the weight of the ethyl methacrylate grafted L-lactide (HEM-LLA), the catalyst stannous octoate is 0.75% of the HEM-LLA; the initiator triphenylphosphine is 0.35% of the HEM-LLA.
[0074] (4) The HEM-LLA oligomer of step (3) is added to a twin-screw extruder for polymerization reaction, and an antioxidant is added at the same time, and reactive mixing and extrusion granulation are performed at high temperature to finally obtain an ethyl methacrylate grafted polylactic acid copolymer material (HEM-PLLA); based on the weight of the HEM-LLA oligomer, the antioxidant triphenyl phosphite is 0.65% of the HEM-LLA oligomer, and the reactive extrusion temperature of the twin-screw extruder for reactive mixing and extrusion granulation is 185°C.
[0075] Performance characterization: The right-angle tear strength of the ethyl methacrylate grafted polylactic acid copolymer material was measured to be 153 kN / m, the elongation at break was 54%, the glass transition temperature was 92 °C, and the molecular weight of the polymer was 2.56 × 10 5 The ethyl methacrylate grafting rate of the polymer was determined to be 40.2% by chemical titration. The presence of terminal hydroxyl groups was determined by chemical titration.
[0076] Example 5
[0077] (1) L-lactide and ethyl methacrylate were added to a reactor, and dicumyl peroxide (DIPO) was added as an initiator. The reaction was carried out at a constant temperature under a nitrogen flow and vacuum conditions to obtain ethyl methacrylate grafted onto L-lactide. The grafting modification reaction temperature was 110°C, the reaction pressure was 55 kPa, the reaction time was 4 hours, and the nitrogen flow rate was 4 m / s. Based on the weight of L-lactide, the ethyl methacrylate content was 280% of the L-lactide, and the dicumyl peroxide content was 5% of the L-lactide.
[0078] (2) The L-lactide that did not participate in the grafting reaction in step (1) was removed by vacuum distillation to obtain purified ethyl methacrylate grafted L-lactide (HEM-LLA); the vacuum distillation temperature was 135° C.; the pressure was 30 kPa, and the time was 3.5 h.
[0079] (3) Prepolymerizing the ethyl methacrylate grafted L-lactide (HEM-LLA) obtained in step (2) at low temperature under the action of a catalyst and an initiator, while adding a nitrogen flow and negative pressure to obtain a HEM-LLA oligomer; the reaction temperature of the low temperature prepolymerization is 140° C., the reaction time is 5 h, the reaction pressure is 400 kPa, the gas flow rate of the nitrogen flow protection is 4 m / s, and based on the weight of the ethyl methacrylate grafted L-lactide (HEM-LLA), the catalyst stannous octoate is 0.8% of the HEM-LLA; and the initiator triphenylphosphine is 0.4% of the HEM-LLA.
[0080] (4) The HEM-LLA oligomer of step (3) is added to a twin-screw extruder for polymerization reaction, and an antioxidant is added at the same time, and reactive mixing and extrusion granulation are performed at high temperature to finally obtain an ethyl methacrylate grafted polylactic acid copolymer material (HEM-PLLA); based on the weight of the HEM-LLA oligomer, the antioxidant triphenyl phosphite is 0.7% of the HEM-LLA oligomer, and the reactive extrusion temperature of the twin-screw extruder for reactive mixing and extrusion granulation is 190°C.
[0081] Performance characterization: The right-angle tear strength of the ethyl methacrylate grafted polylactic acid copolymer material was measured to be 148 kN / m, the elongation at break was 46%, the glass transition temperature was 89 °C, and the molecular weight of the polymer was 2.37 × 10 5 The ethyl methacrylate grafting rate of the polymer was determined to be 39.1% by chemical titration. The presence of terminal hydroxyl groups was determined by chemical titration.
[0082] Comparative Example 1
[0083] First, L-lactide is polymerized and then grafted to prepare a polylactic acid graft copolymer:
[0084] (1) L-lactide (LLA) is prepolymerized at low temperature in the presence of a catalyst and an initiator under a nitrogen flow and negative pressure to obtain LLA oligomers. The reaction temperature for the low temperature prepolymerization is 130° C., the reaction time is 3 hours, the reaction pressure is 300 kPa, the flow rate of the nitrogen flow is 3 m / s, and the amount of the catalyst, stannous octoate, added is 0.5 wt% of the amount of LLA used; and the amount of the initiator, triphenylphosphine, added is 0.2 wt% of the amount of LLA used.
[0085] (2) The LLA oligomer prepared in step (1) is added to a twin-screw extruder for polymerization reaction, and ethyl methacrylate and an antioxidant are added at the same time, and the mixture is reactively mixed and extruded at high temperature to produce granules, thereby finally obtaining an ethyl methacrylate grafted polylactic acid material (HEM-PLLA); based on the weight of the LLA oligomer, the amount of ethyl methacrylate added is 25 wt% of the amount of the LLA oligomer used (and the inventors have experimentally verified that even if the amount of ethyl methacrylate added is further increased, the grafting rate does not increase), the amount of the antioxidant triphenyl phosphite added is 0.5 wt% of the amount of the LLA oligomer used, and the reaction extrusion temperature of the twin-screw extruder for reactive mixing and extrusion granulation is 180°C.
[0086] Product performance: The right-angle tear strength of the ethyl methacrylate grafted polylactic acid copolymer material was measured to be 108KN / m, the elongation at break was 15%, the glass transition temperature was 65°C, and the molecular weight of the polymer was 1.8×10 5 The ethyl methacrylate grafting rate of the polymer was determined to be 1.6% by chemical titration.
[0087] The presence of terminal hydroxyl groups could not be detected by chemical titration.
Claims
1. An unsaturated aliphatic ester grafted polylactic acid copolymer, characterized in that: It is a compound having the general structure of formula I: Where R1, R2, ... and R n are independently selected from H or wherein R is a C1-C6 substituted or unsubstituted alkyl group, preferably a C1-C4 substituted or unsubstituted alkyl group, and R1, R2, ... and R n for The number of groups accounts for R1, R2, ... and R n The molar percentage of the total amount is not less than 25%, preferably not less than 30%, further preferably not less than 35%, and most preferably not less than 40%.
2. The polylactic acid graft copolymer according to claim 1, characterized in that Its right-angle tearing strength is not less than 130kN / m, and its elongation at break is not less than 35%.
3. The copolymer according to claim 1, characterized in that Its weight average molecular weight is 1.5×10 5 -4.5×10 5 .
4. The copolymer according to claim 1, characterized in that Its glass transition temperature is 85-100°C.
5. The method for preparing the unsaturated aliphatic ester grafted polylactic acid copolymer according to claim 1, comprising the following contents: (1) L-lactide, and an initiator to react with each other to obtain an unsaturated fatty ester grafted L-lactide product HEM-LLA, which is purified; wherein, Wherein R is a C1-C6 substituted or unsubstituted alkyl group; (2) mixing the HEM-LLA obtained in (1) with a catalyst and an initiator, and prepolymerizing at low temperature to obtain a HEM-LLA oligomer; (3) The HEM-LLA oligomer obtained in (2) is mixed with an antioxidant and polymerized at high temperature to obtain an unsaturated aliphatic ester grafted polylactic acid copolymer.
6. The preparation method according to claim 5, characterized in that In step (1), the initiator is dicumyl peroxide or 2,5-dimethyl-2,5-bis-(tert-butylperoxy)hexane, and the amount of the initiator added is 1-10% by weight of L-lactide.
7. The preparation method according to claim 5, characterized in that: Step (1) is a constant temperature reaction under inert gas flow and vacuum conditions, the reaction temperature is 50-150° C., the reaction pressure is 2-100 kPa, and the reaction time is 1-20 h.
8. The preparation method according to claim 5, characterized in that: The It is one or more of methyl methacrylate, ethyl methacrylate and butyl methacrylate.
9. The preparation method according to claim 5, characterized in that: Based on the weight of L-lactide, The addition amount is 150-350% of L-lactide.
10. The preparation method according to claim 5, characterized in that: The purification in step (1) is to remove the L-lactide that does not participate in the grafting reaction by vacuum distillation to obtain purified unsaturated aliphatic ester-grafted L-lactide.
11. The preparation method according to claim 5, characterized in that: The catalyst in step (2) is selected from one or more of stannous octoate, zinc lactate, trialkylaluminum, triisobutylaluminum and stannous chloride. The amount of the catalyst added is 0.1-5% by weight of the HEM-LLA.
12. The preparation method according to claim 5, characterized in that: The initiator in step (2) is selected from at least one of glycerol, xylitol, ethylene glycol and triphenylphosphine, and the amount of the initiator added is 0.05-5.0% by weight of the HEM-LLA.
13. The preparation method according to claim 5, characterized in that: Step (2) is low-temperature polymerization under inert gas flow and negative pressure conditions, the polymerization reaction temperature is 100-150° C., the reaction time is 2-15 hours, and the reaction pressure is 100-1000 kPa.
14. The preparation method according to claim 5, characterized in that: The antioxidant in step (3) is one of phosphites, alkyl polyphenols and thiobisphenols, and the amount of the antioxidant added is 0.1%-5% by weight of the HEM-LLA oligomer.
15. The preparation method according to claim 5, characterized in that: The temperature of the polymerization reaction in step (3) is 150-250°C.
16. The preparation method according to claim 5, characterized in that: In step (3), a twin-screw extruder is used to realize the reaction process, HEM-LLA oligomer and antioxidant are added into the twin-screw extruder for polymerization reaction, and high-temperature reactive mixing and extrusion granulation are performed to obtain a polylactic acid graft copolymer.
17. Use of the unsaturated fatty ester grafted polylactic acid copolymer according to claim 1, wherein the copolymer is used in the fields of agricultural mulch films, food packaging and medical hygiene products.
Citation Information
Patent Citations
Preparation method of polylactic acid grafted copolymer
CN105542089A
Polylactic acid copolymer and preparation method thereof
CN115785415A
Process for preparing surface lactic acid graft modified starch and aliphatic polyester graft copolymer
CN1693341A
Method of grafting functional groups to synthetic polymers for making biodegradable plastics
WO1997047670A1